Hybride Werkstoffsysteme: Systematische Betrachtung und Bewertung der physikalischen Wirkmechanismen - Hummelberger, David (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2019)
Hybrid material systems result from the specific combination of different materials. For optimized design of hybrid material systems for structural components, a profound fundamental understanding regarding the interaction of the different materials is of great importance. This work systematically investigates adhesively bonded hybrid material systems and assesses the underlying mechanisms with experimental and numerical methods.